PELESTARIAN IKAN BILIH (Mystacoleucus padangensis) MELALUI PENGEMBANGAN AGROWISATA PERIKANAN DI DANAU SINGKARAK SUMATERA BARAT - Gunarto, Anton (BPPT)
Singkarak Lake located in Solok Regency and Tanah Datar Regency potentially for tourism and fi-shery sector because of its scenic view and bilih fi sh specialization. That sector cohesiveness creates a fi shery agro tourism practices. However dilemmas shows, such as overlapping of tourism interest with bilih fi sh conservation. Objective of this study are learn about potential and conservation efforts for bilih fish and analysis its relevancy with tourism aspect, so it will gain a modeling concept of Developing Area of Bilih Fish Agro tourism (“Kembang Aibil”) in particular Singkarak Lake area. A proposal concept is agro tourism landscape arrangement with zoning system. Zoning objectiveis to accommodate tourism interest with bilih conservation through separated area based on visitor activi-ties. Singkarak lake as unique and interesting recreation place for tourists because its bilih fi sh exis-tence. Singkarak lake zoning divide into three zones: (1)Recreation zone is singkarak quay area, (b) buffer zone is Singkarak Lake Public Fishery Water Unit (UPPU), and (c) Conservation zone is Bilih Fishery Preservation in Sumpur and Paninggahan River in Sumpur village, South Batipuh Sub district, Tanah Datar regency and Bilih Conservation Centre in Nagari Guguak Malalo.Key words : Tourism, Fishery Agro Tourism and Bilih Fish